The Relationship Between Self Efficacy and Stress Management Ability with Academic Achievement in Students of SMAN 9 Padang - Venny Anisa Putri; Linda Fitria; Mufadhal Barseli (Journal Of Psychology, Counseling And Education, 2025)
This study aims to determine the relationship between self-efficacy and the ability to manage stress with academic achievement in students of SMAN 9 Padang in the academic year 2024/2025. The type of research used in this study is quantitative. The population of this study amounted to 403 people enrolled in the 2024/2025 school year, with a sample of 200 people taken using proportionate stratified random sampling. This study examines the relationship between Self Efficacy and Ability to Manage Stress with Academic Achievement, the instruments used to collect data in this study are questionnaires and student learning outcomes arranged according to the Likert model. Data analysis was carried out using a statistical program on an SPSS 25 computer and Microsoft Excel. Based on the results of the hypothesis, a correlation value of 0.245 was obtained. And obtained the coefficient of determination (R Squared) of 0.060 which contains the relationship of self efficacy variables and managing stress on academic achievement by 6% and the rest is influenced by other variables. So it can be concluded that there is a significant relationship between self efficacy and the ability to manage stress with a p value of 0.060.